2015
DOI: 10.1139/cjm-2015-0166
|View full text |Cite
|
Sign up to set email alerts
|

Creating a customized intracellular niche: subversion of host cell signaling byLegionellatype IV secretion system effectors

Abstract: Abstract:The Gram-negative facultative intracellular pathogen Legionella pneumophila infects a wide range of different protozoa in the environment and also human alveolar macrophages upon inhalation of contaminated aerosols. Inside its hosts, it creates a defined and unique compartment, termed the Legionella-containing vacuole (LCV), for survival and replication. To establish the LCV, L. pneumophila uses its Dot/Icm type IV secretion system (T4SS) to translocate more than 300 effector proteins into the host ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 176 publications
0
30
0
2
Order By: Relevance
“…Legionella species encode a type IVb secretion system (T4bSS), known as the Dot/Icm apparatus, which translocates over 300 bacterial effector proteins directly into the host cytosol [2022]. The T4bSS is required for intracellular survival and deletion mutants lacking single structural components of the Dot/Icm apparatus are avirulent because they fail to block endocytic maturation [23–25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legionella species encode a type IVb secretion system (T4bSS), known as the Dot/Icm apparatus, which translocates over 300 bacterial effector proteins directly into the host cytosol [2022]. The T4bSS is required for intracellular survival and deletion mutants lacking single structural components of the Dot/Icm apparatus are avirulent because they fail to block endocytic maturation [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…The T4bSS is required for intracellular survival and deletion mutants lacking single structural components of the Dot/Icm apparatus are avirulent because they fail to block endocytic maturation [23–25]. Collectively, the Dot/Icm effector proteins facilitate niche biogenesis and homeostasis [20,22]. One example is the SdhA effector, which maintains LCV integrity by counteracting, through an unknown mechanism, the activity of the secreted Legionella phospholipase PlaA [18].…”
Section: Introductionmentioning
confidence: 99%
“…rapidly depart the endocytic pathway by modifying their PV (called the inclusion) to resemble a Golgi-derived exocytic vacuole (23), further customizing it with a family of chlamydial proteins called Incs that mediate many crucial interactions with host signaling molecules and organelles (24). In contrast, the Legionella-containing vacuole (LCV) more closely resembles the ER, although its association with many different host Rab GTPases that are often not found on the same host membrane makes the LCV a distinctive subcellular compartment (25). Coxiella burnetii is a unique bacterial pathogen that replicates in what is essentially a mature phagolysosome (26).…”
mentioning
confidence: 99%
“…The Dot/Icm machinery is the T4SS in Legionella spp. and is responsible for hundreds of effector proteins throughout the infection cycle (So et al, 2015). Epitope-tagging one of these effectors, LncP, enabled fluorescence imaging of infected macrophages and showed that the protein was secreted from the bacterial cytoplasm by the T4SS and ultimately translocated across a remarkable five membranes in order to be assembled into the mitochondrial inner membrane of the host cell (Dolezal et al, 2012).…”
Section: Type 4 Secretion System (T4ss)mentioning
confidence: 99%